Glossary quality in education and training - (:unkn) unknown (Publications Office of the European Union, 2011)
This "glossary of terms on quality in education and training is meant to promote communication and understanding between countries. It is intended for all stakeholders in education and VET, researchers; experts; those involved in improving learning curricula; and education and training providers. While it does not represent an exhaustive inventory of the terminology used by specialists, the glossary - an updated and extended version of 'Quality in training / La qualité dans la formation' published by Cedefop in 2003 - takes into account recent EU policy developments, including the creation of the European qualifications framework for lifelong learning (EQF) and the development of a European credit system for vocational education and training (ECVET)." (Hrsg., BIBB-Doku)
Glossar Qualität in der allgemeinen und beruflichen Bildung
Glossaire qualité dans l'enseignement et la formation
Keywords: Glossar; Qualität; Berufsbildung